(3GdCSS GdYdejI h GdYedjI aj GdeMGSHI GdMchejI (B:s (3OQGSI fXQjI h JWHjbjI (B/s - (3GdHfG, HTjQ YHO GdMajXs ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2011)
(3GdGWGQ GdfXQj ddeMGSHI GdMchejI , fXGe GdeMGSHI GdMchejI aj LeghQjI eUQ GdYQHjI , eaghe h WHjYI GdehGRfI GdYGeI ddOhdI h GdehGRfI GdYGeI ddOhdI aj LeghQjI eUQ GdYQHjI h CNjQG eONd ebJQM dJWhjQ GdehGRfI GdYGeI aj GdOhd GdfGejI (B.s
(3eQGLY U(B.333s
Keywords: (3GdeMGSHI GdMchejIs; (3GdejRGfjIs; (3JObjb GdMSGHGJ GdMchejIs